Nano-fabrication of cellular force sensors and surface coatings via dendritic solidification - Paneru, Govind (Kansas State University, 2014)
Directed electrochemical nanowire assembly (DENA) is a method for fabricating nano-structured materials via electrochemical dendritic solidification. This thesis presents two new applications of nano-structured materials that are fabricated via the DENA methodology: cellular force sensors to probe adhesive sites on living cells and single-crystalline metallic dendrites as surface coating materials. Fast migrating cells like D. discoideum, leukocytes, and breast cancer cells migrate by attachment and detachment of discrete adhesive contacts, known as actin foci, to the substrate where the cell transmits traction forces. Despite their importance in migration, the physics by which actin foci bind and release substrates is poorly understood. This gap is largely due to the compositional complexity of actin foci in living cells and to a lack of technique for directly probing these sub-cellular structures. Recent theoretical work predicts these adhesive structures to depend on the density of adhesion receptors in the contact sites, the receptor-substrate potential, and cell-medium surface tension. This thesis describes the fabrication of sub-microscopic force sensors composed of poly(3,4-ethylene dioxythiophene) fibers that can interface directly with sub-cellular targets such as actin foci. The spring constants of these fibers are in the range of 0.07-430 nN m-1. These fibers were used to characterize the strength and lifetime of adhesion between the single adhesive contacts of D. discoideum cells and the fibers, finding an average force of 3.1 ± 2.7 nN and lifetime of 23.4 ± 18.5 s. This capability is significant because direct measurement of these properties will be necessary to measure the cell-medium surface tension and to characterize the receptor-substrate potential in the next (future) stage of this project. The fabrication of smart materials that are capable of the high dynamic range structural reconfiguration would lead to their use to confer hydrophobic, lipophobic, and anti-corrosive character to substrates in a regenerative manner. As a step towards this goal, we have extended the DENA method to enable repetitive growth and dissolution of metallic dendrites to substrates. The experimental parameters that control this process are the frequency and duty cycle of the alternating voltage signal that initiates the dendritic growth.
Keywords: Nanowire fabrication; Cellular force sensors; D. Discoideum; Physics (0605)